Study of User Perception of A Room (Case Study: Architecture Building) - Ulfa Auliyah; M. Nawawiy Loebis (International Journal of Architecture and Urbanism, 2019)
Space cannot be separated from human life, both psychologically emotional (perception) and dimensional. Humans are moving and living, thinking, and also creating space to express the shape of their world and formed when people react to the environment in giving meaning to their environment. It can be said that environmental evaluation, furthermore, is a response to the overall influence of a detailed analysis of specific aspects, and more of a compared to the manifest function and is strongly influenced by images. This paper explains the results of the study, which intends to find out student perceptions of the meaning of space in the Architectural building of the Faculty of Engineering, University of North Sumatra. The study uses data analysis methods. The results of the study show that students' perceptions of space use are not by the allocation of the Department of Architecture, Faculty of Engineering, University of North Sumatra, because it is influenced by culture, space settings, and accessibility. The benefits of this study as a reference to the Department of Architecture of the University of North Sumatra to be able to improve the quality of teaching and to learn in supporting the comfort of student learning.